(untitled) (International Journal of Engineering and Computer Science, 2018)
Annotations are useful in effective information retrieval. Annotation can be applied to several fields like image, videos, documents, etc. Annotation helps to understand and retrieve the documents very easily. For doing annotation, firstly important attributes have to be identified. Making annotations on documents is a hardwork because people have to read the documents fully to think which sentences have to be annotated. If people are automatically given the sentences which are most suitable for annotations, it is more easier. Also annotations can be done to webpage-metadata also. In this paper, a survey about annotations is discussed and a brief description about proposed methodology is given.